Impatiens x New Guinea Hybrids New Guinea Impatiens - Edward Gilman; Teresa Howe (EDIS)
This document provides an overview of the New Guinea impatiens, a versatile and colorful annual plant. It highlights the plant’s distinguishing features, including its brilliantly marked foliage, large single flowers in various colors, and its ability to tolerate greater amounts of sun once established. The document details the plant’s growth habits, ideal planting conditions, and maintenance requirements, emphasizing its suitability for edging, mass planting, and container gardening. Additionally, it mentions the plant’s pest resistance and recent developments in seed propagation, making it a popular choice for gardeners. Original publication date October 1999.